Knowledge translation: putting the 'practice' in evidence-based practice. - MacDermid JC; Graham ID (Hand Clinics, 2009)
Knowledge translation (KT) is an iterative process that involves knowledge development, synthesis, contextualization, and adaptation, with the expressed purpose of moving the best evidence into practice that results in better health processes and outcomes for patients. Optimization of the process requires engaged interaction between knowledge developers and knowledge users. Knowledge users include consumers, clinicians, and policy makers. KT is highly reliant on understanding when research evidence needs to be moved into practice. Social, personal, policy, and system factors contribute to how and when change in practice can be accomplished. Evidence-based practitioners need to understand a conceptual basis for KT and the evidence indicating which specific KT strategies might help them move best evidence into action in practice. Audit and feedback, knowledge brokering, clinical practice guidelines, professional standards, and 'active-learning' continuing education are examples of KT strategies.Copyright © 2009 by Elsevier Inc.